The fading flame of hope: the climatic and environmental emergency in the eyes of Polish pupils and students - Cywiński, Aleksander (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2023)
The author’s motivation for undertaking this research was his own anxieties; anxieties arising from the global ecological and environmental emergency. The aim of my research was to determine young people’s awareness of the climate emergency and their agency (possible actions) related to remedying this phenomenon. In conducting the research, a mixed quantitative and qualitative strategy was used with an online survey, thus examining the opinions of the respondents. The text analyses the answers to questions eliciting opinions on the climate and environmental emergency (a term used in one of the European Parliament’s relevant resolutions), with particular regard to the possibility of stopping the aforementioned crisis. Respondents were primary and secondary pupils, and university students. Among the conclusions, the following should be singled out: 90.3% of respondents agree that we are dealing with an ecological and environmental emergency, but only 12.5% believe that we will stop the crisis, while 29.8% do not, and 57.7% do not know. Most importantly, the analysis of young people’s statements reveals the pessimistic nature of their opinions, revealing the fading hope of remedying the emergency. In combination with the literature review, this sends an alarming message about the need to act not only to deal with the crisis but also in the field of information addressed to all social groups. In summary, there is evident fear that predictions of disaster may turn out to be self-fulfilling prophecies (as defined by Robert K. Merton). The demonstrated ability of young people to influence politicians offers us a hope that we might prevent such a disaster. For such action to succeed, it needs to take place both inside and outside of schools and universities.